LEK – Längsschnittliche Erhebung pädagogischer Kompetenzen von Lehramtsstudierenden: Zur Entwicklung von bildungswissenschaftlichem Wissen. - Seifert, Andreas; Schaper, Niclas (AEPF-Tagung “Baustelle Lehrerbildung”)

Überprüfung eines Kompetenzmodells und Messinstruments zur Strukturierung allgemeiner pädagogischer Kompetenz in der universitären Lehrerbildung. - Seifert, Andreas; Schaper, Niclas (Lehrerbildung auf dem Prüfstand)

Entwicklung und empirische Überprüfung eines phasenübergreifenden Berufsfähig-keitsprofils für angehende Lehrpersonen. - Israel, Georgq; Seifert, Andreas; König, Johannes; Schaper, Niclas; Blömeke, Sigrid (AEPF-Tagung „Mixed Methods in der empirischen Bildungsforschung”)

My Mother: My Best Friend? Adults’ Relationships with Significant Others Across the Lifespan - Buhl, Heike M. (Journal of Adult Development)
In order to investigate the significance of adults’ relationship to their parents, this relationship is compared to relationships with siblings, friends, partners, and children. German adults (N = 902) between the ages of 20 and 86 completed the Network of Relationships Inventory (Furman and Buhrmester 1992). Participants felt most supported by their partners, followed by their children, mothers, friends, fathers, and siblings. Conflicts were more frequently found within the family (especially with the partner, followed by children, mothers, fathers, and siblings) than with friends. Except for partner relationships, both conflict and support decreased with age. Concerning relative power within their relationships, partners, mothers, and siblings are seen as equals, friends and especially fathers are perceived as more powerful, and children as less, yet increasingly powerful. Regarding all relationship types and relationship qualities, the differences between women and men were small.
Keywords: Family; Friends; Support; Conflict; Power

Zusammenhänge zwischen der Fähigkeit zur Perspektivenübernahme und dem Textverstehen im Vor- und Grundschulalter - Buhl, Heike M.; Möller, Franziska; Oebser, Manuela; Stein, Freia; Noack, Peter (Diskurs Kindheits- und Jugendforschung)
Im vorliegenden Beitrag wird der Zusammenhang zwischen der Fähigkeit zur Perspektivenübernahme und sinnverstehendem Lesen dargestellt. Auf der Grundlage von Arbeiten zum Textverstehen sowie zu Perspektivenübernahme und Theory of Mind wurde ein positiver Zusammenhang zwischen Perspektivenübernahmefähigkeit und Textverstehensleistung erwartet. Diese Hypothese wurde an zwei Stichproben unterschiedlichen Alters geprüft: In der ersten Studie beantworteten 37 Vorschulkinder Fragen zu vorgelesenen Geschichten sowie Perspektivenübernahme-Aufgaben. Zwischen den Bereichen fand sich eine deutliche positive Korrelation, die bei Kontrolle der Intelligenz erhalten blieb. An der zweiten Studie nahmen 69 Grundschulkinder der dritten Jahrgangsstufe teil, die Texte lasen und Aufgaben dazu wie auch zur Perspektivenübernahme bearbeiteten. In dieser Stichprobe fand sich der erwartete Zusammenhang ausschließlich in der Teilgruppe der guten Leser. Er blieb bei Kontrolle der Intelligenz erhalten. Die Ergebnisse werden auch in Hinblick auf die Förderung der Lesekompetenz diskutiert.
Keywords: Textverstehen; Lesekompetenz; Perspektivenübernahme; Theory of Mind; Kindesalter

Entwicklung und psychometrische Überprüfung eines Messinstruments zur Erfassung pädagogischer Kompetenzen in der universitären Lehrerbildung. - Seifert, Andreas; Hilligus, Annegret Helen; Schaper, Niclas (Lehrerbildung auf dem Prüfstand)

LEK – Längsschnittliche Erhebung pädagogischer Kompetenzen von Lehramtsstudierenden: Testinstrumente, Forschungsdesign und Fragestellungen. - König, Johannes; Seifert, Andreas; Blömeke, Sigrid; Schaper, Niclas (AEPF-Tagung „Selbstregulation – Fremdregulation“)

Welche Dimensionen bzw. Modellstruktur liegt der Messung pädagogischer Kompetenz in der universitären Lehrerausbildung zugrunde? - Seifert, Andreas; Schaper, Niclas (AEPF-KBBB-Tagung)

Special Section on Individuation during late adolescence and emerging adulthood: German studies (International Journal of Behavioral Development)

Development of a model describing individuated adult child-parent relationships - Buhl, Heike M. (International Journal of Behavioral Development)
This study investigates age-related changes and dyadic-specific differences in adult child–parent relationships. Using an individuation framework, two German samples of 224 and 105 participants aged between 21 and 47 years were administered the Network of Relationships Inventory, the Emotional Autonomy Scale and the Authority Reciprocity Questionnaire. Factor analyses resulted in a measurement model valid for adult children, their mothers and fathers. The model includes connectedness (with emotional and cognitive aspects) as well as individuality (assessed as power symmetry). Connectedness decreased with age. Symmetry in father–child relationships increased over time, while mother–child relationships were perceived to be symmetrical by early adulthood. Child–mother relationships were more connected than child–father relationships. Sons described themselves as more powerful than did daughters.
Keywords: adult child–parent relationships; adulthood; connectedness; Germany; individuation; symmetry

Ein erweitertes individuationstheoretisches Modell zur Vorhersage der aktuellen und geplanten Unterstützung Erwachsener für ihre Eltern - Buhl, Heike M. (Intergenerationelle Transferleistungen in Familien)

Individuation during adolescence and emerging adulthood – Five German studies - Reis, Olaf; Buhl, Heike M. (International Journal of Behavioral Development)
Among theories describing human relationships and interactions, individuation theory has increasingly gained attention over the last three decades. After ideas of individuation were introduced to the USA by German emigrants, such as Erik Erikson and Peter Blos, a second generation of American researchers brought the issue to the fore during the 1980s. Since then, German research has taken up the topic. Current lines of German research resonate with contemporary American research (e.g., Allen, Smetana), but also explore possible extensions of the theory. Here we introduce five German studies that explore relations between individuation and attachment, interactions between transmissions and relationships, or try to extend individuation theory beyond adolescence and the family system.

Significance of individuation in adult child-parent relationships - Buhl, Heike M. (Journal of Family Issues)
This study investigates the significance of adult children's individuation for the adult child—parent relationship. Following Youniss, individuation was assessed via its dimensions of both connectedness and individuality. A sample of 349 participants between 20 and 47 years of age were given questionnaires containing scales from the Network of Relationships Inventory among others. Individuation predicted satisfaction, intimacy, and conflict. The combination of connectedness and individuality did not have any impact on relationship quality. The significance of children's individuation did not differ between young and middle-aged adults.

Erste Ergebnisse zur Messung pädagogischer Kompetenz in der universitären Lehrerausbildung. - Seifert, Andreas; Schaper, Niclas (Tagung „Kompetenzdiagnose und Kompetenzentwicklung in der Lehrerbildung“ des CEVET und PLAZ)

Messung erziehungswissenschaftlicher Kompetenz in der Lehrerausbildung. - Seifert, Andreas; Schaper, Niclas; Hilligus, Annegret Helen; Grafe, Silke (AEPF-Tagung „Kompetenz – Modellierung – Diagnostik – Entwicklung – Förderung“)

Die Beziehung zwischen Erwachsenen und ihren Eltern. Individuation und biographische Übergänge - Buhl, Heike M.

Emerging adulthood in Europe. Common traits and variability across five European countries - Buhl, Heike M.; Lanz, Margherita (Journal of Adolescent Research)
The fact that there is a specific age marking the emergence of adulthood in the United States has been well documented. The starting point for the studies included in this special issue is the assumption that the same can be said for European countries. Thus, a comparison of characteristics of emerging adulthood between different European countries was performed. In this special issue, contributions of scholars from five different European countries are taken as representative of different regions: Spain, Italy, Finland, Germany, and the Czech Republic. The efforts of the research are twofold. The first is to look at how the traditional markers of adulthood have changed and how the concept of adulthood is seen in the different countries. The second is to highlight the influence that the entrance into the working world and romantic partnership have on emerging adults and to detect the impact of the timing of entering adulthood on identity achievement. The results are presented here as different pathways that emerging adults follow to reach the same goal of mature adulthood.

Gefährlichkeitseinschätzung von Autofahrern, Motorradfahrern und Radfahrern. Psychometrische Modellierung der Prognose durch verschiedene Gefahrenaspekte und ihr Beitrag zur Klärung von Unterschieden zwischen jungen und nicht-jungen Verkehrsteilnehmern. - Seifert, Andreas

Well-being and the child-parent relationship at the transition from university to work life - Buhl, Heike M. (Journal of Adolescent Research)
This longitudinal study addresses the impact of the transition from university to work life on emerging adults' well-being and their relationship with their parents. A sample of 102 German students attending their last year at the university (M = 25.44 years, SD = 2.61) completed a questionnaire. Among others, scales from the Network of Relationships Inventory and symptom checklists were administered. Four years later, 51 employed participants of the initial sample were contacted again. During the transition from university to work life, well-being and the relationship with their parents improved. Following a typological approach, two groups of emerging adults were revealed by means of cluster analyses. Well-being in one group increased, whereas well-being in the second group decreased. Group membership was predicted by sex, personality, and the child–parent relationship in university times.

Kommunikative Regulation und sprachlicher Ausdruck von Soll-Ist-Diskrepanzen in mündlichen und schriftlichen Äußerungen - Buhl, Heike M.; Hofer, Manfred; Lege, Thomas (Zeitschrift für Psychologie)
Der Regulationstheorie der Sprachproduktion folgend gibt eine Ist-Soll-Diskrepanz jenseits tolerierbarer Grenzen ggf. den Anstoß zum Sprachproduktionsprozess, der in eine Äußerung mündet (vgl. Herrmann & Grabowski, 2003). Wir nehmen an, dass die Stärke der Ist-Soll-Diskrepanz die Häufigkeit der Verbalisierung von Soll- und Ist-Informationen in der sprachlichen Äußerung beeinflusst. Bei starkem Ziel werden mehr Soll-Informationen erwartet als bei schwachem Ziel. In zwei Rollenspielexperimenten wurden Äußerungen Jugendlicher in Konfliktgesprächen mit der Mutter erhoben, wobei die Stärke der Ist-Soll-Diskrepanz, operationalisiert über die Bedeutsamkeit des Zieles in einer Konfliktsituation, variiert wurde. Um Einflüssen der Kommunikationssituation nachzugehen, wurde das erste Experiment mündlich (N = 53), das zweite schriftlich (N = 131) durchgeführt. Insgesamt wurden schriftlich mehr Soll-Informationen verbalisiert. Im mündlichen Rollenspielexperiment fanden sich wie erwartet bei starkem Ziel mehr Soll-Informationen als bei schwachem Ziel. Im schriftlichen Rollenvorstellungsexperiment dagegen waren bei starkem Ziel sogar weniger Soll-Informationen zu verzeichnen, was unter Berücksichtigung situationaler Unterschiede zwischen mündlicher und schriftlicher Sprachproduktion diskutiert wird.